(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Purpose of this study are analyze financial lease advantage through analyze and discuss financial lease cost, and achieve tax advantage to reach study objective. study include two firms ,oil firm and construction firm with limited liability. The inductive method is used for the applied part in analyzing the financial data of the companies considered in 2011-2015.The result of the study shows that the financial lease achieve present value of the costs is positive. This study found out the results that verify the hypothesis: The tax advantage of financial Leasing is characterized by decreasing cost and achieving higher tax shield. The study also found the most important recommendations of awareness of the benefits arising from finance lease activity and its impact on the company level and at the level of the national economy and take advantage of the high tax rate for the company to achieve tax shield to the company the benefit of the tax reduction.